2015
DOI: 10.1080/00207543.2015.1012605
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Shewhart-type rank based control charts for monitoring location parameters of univariate processes

Abstract: The nonparametric (distribution-free) control charts are robust alternatives to the conventional parametric control charts when the form of underlying process distribution is unknown or complicated. In this paper, we consider two new nonparametric control charts based on the Hogg-Fisher-Randle (HFR) statistic and the Savage rank statistic. These are popular statistics for testing location shifts, especially in right-skewed densities. Nevertheless, the control charts based on these statistics are not studied in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 42 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…The values of the plotting statistics for SC and SL charts, along with test samples, are reported in Table 6 and their corresponding control charts are given in Figure 4. [4] which concluded that there is no scale shift in the process.…”
Section: Illustrative Examplementioning
confidence: 99%
See 2 more Smart Citations
“…The values of the plotting statistics for SC and SL charts, along with test samples, are reported in Table 6 and their corresponding control charts are given in Figure 4. [4] which concluded that there is no scale shift in the process.…”
Section: Illustrative Examplementioning
confidence: 99%
“…[5]). The shift in location is noted when p 3 is very low except p 4 ; if p 3 is relatively high except p 4 , then there is the indication of a shift in scale. If both p 3 and p 4 are very low, shift is noted in both location and scale.…”
Section: Description Of Sc and Sl Chartsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qiu and Hawkins, Bakir, Qiu, and Chatterjee and Qiu, among others, paid lots of attention to NSPM tools and techniques in the initial years of the 21st century. Among the more recent articles, we recommend Li et al, Qiu and Li, Graham et al, Abbasi et al, Mukherjee et al, Graham et al, Liu et al, Chowdhury et al, Mukherjee and Sen, Qiu and Zhang, Mukherjee, Chong et al, and Huang et al Clearly, in the last few years, research on NSPM techniques has gained considerable momentum. Mukherjee and Marozzi outlined the phenomenal growth of works on NSPM schemes.…”
Section: Introductionmentioning
confidence: 99%
“…They noted a nearly 200% growth on research in nonparametric process control charts in the first half of the current decade. Interested readers may see Chakraborti and Graham (2007), Chakraborti et al (2011), Graham et al (2012Graham et al ( , 2014, Mukherjee and Chakraborti (2012), Mukherjee et al (2013), Balakrishnan et al (2015) Mukherjee and Sen (2015), Li et al (2016) and Mukherjee and Marozzi (2016b) among others for various aspects of nonparametric control charts. Some other recent works include Hawkins and Deng (2010) who considered a nonparametric control chart under a change-point set-up and Abbasi et al (2013) who considered a nonparametric control chart for the progressive mean.…”
Section: Introductionmentioning
confidence: 99%